GIS Untuk Pemetaan Dan Pencarian Lokasi Rumah Sakit di Kota Solok - Alif Pagar Alam; sularno (Journal Of Informatics And Busisnes, 2024)
Hospitals are one of the public facilities owned by the government and the private sector which have a very strategic role in efforts to improve public services. So every community member is expected to know the locations of the hospitals closest to where they live to anticipate undesirable things. Creating a web-based hospital Geographic Information System (GIS) has the aim of the hospital's existence. The decision to choose the right and quick hospital is an important decision and at worst it could result in losing someone's life. GIS can represent the real world on a computer monitor just as a map sheet can represent the real world on paper. This system is very useful in making it easier for the public to see the location of hospitals in the city of Solok. The aim of this research is to build a geographic information system with an integrated database, especially to find the location of hospitals in the city of Solok. So it can provide information to users who want to find hospital locations in the city of Solok.